2022
DOI: 10.1055/s-0041-1737343
|View full text |Cite
|
Sign up to set email alerts
|

Survey of New, Small-Molecule Isatin-Based Oxindole Hybrids as Multi-Targeted Drugs for the Treatment of Alzheimer’s Disease

Abstract: In the last decade, our group has been very active at developing and assaying complex libraries of scaffolds with a focus on their potential to identify bioactive drug candidates for neurodegenerative diseases, particularly Alzheimer’s disease (AD). Attention has been focused on isatin-based oxindole scaffolds, for which promising results concerning butyrylcholinesterase (BuChE) inhibitory activity have previously been obtained. Considering some published reports and detailed analysis of the pharmacophores of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 69 publications
0
9
0
4
Order By: Relevance
“…1 In the last few years, we have focused on neurodegenerative disorders, such as Alzheimer's disease, reporting several families of new isatin-derived small-molecule hybrids with promising activity as cholinesterase inhibitors. 2 Remarkably, we found that some of our isatin-based oxindole families 3 exhibit promising antiproliferative activity in several tumour cell lines. 4 Cancer is one of the leading causes of death worldwide and still a major problem for society and a major challenge for the scientific community.…”
Section: Introductionmentioning
confidence: 83%
“…1 In the last few years, we have focused on neurodegenerative disorders, such as Alzheimer's disease, reporting several families of new isatin-derived small-molecule hybrids with promising activity as cholinesterase inhibitors. 2 Remarkably, we found that some of our isatin-based oxindole families 3 exhibit promising antiproliferative activity in several tumour cell lines. 4 Cancer is one of the leading causes of death worldwide and still a major problem for society and a major challenge for the scientific community.…”
Section: Introductionmentioning
confidence: 83%
“…Por essa razão, foram sintetizados também derivados do tipo espiro-acetal-oxindole através de reações simples de proteção do grupo carbonilo na posição C3 da isatina, utilizando etilenoglicol ou metanol, em meio ácido, em refluxo de tolueno (Esquema 5C) [51]. Recentemente, constatou-se que a proteção do grupo C3 da isatina mostrou ser fundamental para a manipulação das outras posições estruturalmente acessíveis [52,53]. Apesar de quer o etilenoglicol quer o metanol poderem ser usados como agentes de proteção, optou-se essencialmente pelo último pois pode ser facilmente reconvertido no grupo carbonilo utilizando meio ácido, em condições reacionais suaves.…”
Section: Doença De Alzheimer: O Primeiro Desafio 21 Síntese De Novas ...unclassified
“…Tabela 1 -Resultados in vitro de IC 50 relativos à inibição de eeAChE, eqBuChE e hBuChE, determinados para compostos do tipo oxindole-3-substituídos [42,51,53]. De uma forma geral, todos os compostos testados não mostraram atividade relevante na inibição da enzima AChE.…”
Section: Ensaios Biológicos: Colinesterases (Che) Monoamina Oxidases ...unclassified
See 2 more Smart Citations